The Ancient-Turned-New Concept of “Spiritual Hygiene”: An Investigation of Media Coverage of Meditation from 1979 to 2014 - Lauricella, Sharon (Journal of religion and health, 2016)
A spiritual—yet not religious—practice, meditation has been touted as beneficial to boosting the immune system, lowering blood pressure, alleviating migraines, and increasing gray matter in parts of the brain. While scientific research on meditation is beginning to quantify its benefits, there is increasing concern among the scientific community that news outlets glorify the potential benefits of meditation. This paper considers coverage of meditation in mainstream print media by analyzing 764 articles printed in English from worldwide media outlets from 1979 to 2014. Frame theory analysis is employed to better understand how meditation is presented in print media and how the perception of the practice is interpreted by readers. Results indicate that articles reflect the health and wellness challenges present in contemporary culture, together with a desire for personal relief from such issues. The paper suggests that the practice of meditation as “spiritual hygiene” is indicative of a sociocultural shift in which meditative techniques are becoming increasingly recognized, encouraged, and practiced.